The Influence Of Financial Technology (Fintech) And User Experience On Trust In Financial Transactions Mediated By Perceptions Of Security - Santo Dewatmoko; Udayat Udayat; Desy Tri Anggarini (Management Studies and Entrepreneurship Journal (MSEJ), 2023)
This research investigates the intricate interplay of Financial Technology (Fintech), User Experience, Security Perception, and Trust in Financial Transactions within the context of Bank Mandiri's Surapati branch in Bandung. Utilizing a sample of 50 employees, a path analysis employing Partial Least Squares (PLS) was conducted to examine the direct and indirect effects of Fintech and User Experience on Security Perception and Trust in Financial Transactions. The results indicate a highly significant direct impact of Financial Technology (Fintech) on both Security Perception and Trust in Financial Transactions, highlighting the transformative influence of technological advancements in shaping employees' perceptions of security and trust in financial transactions. Conversely, while the direct effect of User Experience on Security Perception was not statistically significant, the indirect effect of User Experience on Trust in Financial Transactions through Security Perception did not reach significance, suggesting that the relationship between user experience and trust is not significantly mediated by security perceptions in this specific context. These findings contribute nuanced insights into the evolving dynamics of Fintech integration, user experiences, and their implications for security perceptions and trust in digital financial services.